Expression of KI-67, FSCNI and TNFRSF 12A in histologically non-involved mucosal surgical margins as predictive markers for local relapse in oral squamous cell carcinoma / Nur Fauziani Zainul Abidin - Nur Fauziani, Zainul Abidin (2020)
Introduction: The presence tumour-related genetic alterations in histologically noninvolved mucosal surgical margins was linked to development of local relapse in OSCC. Aims: The present study aimed to determine the association between expression of Ki67, FSCN1 and TNFRSF12A in histologically non-involved mucosal surgical margins of OSCC patients and local relapse. Materials and methods: The study involved a total of 34 OSCC cases including 15 cases of patients who had relapse within the 5 years followup period and 19 cases of patients who did not had relapse. Two-stage sampling was carried out to select the margins’ site, followed by the representative sections from the selected site. All the selected sections were subjected to FSCN1, TNFRSF12A and Ki-67 immunostaining. The immunostaining for FSCN1 and TNFRSF12A were evaluated by a semi-quantitative approach (HSCORE), while Ki-67 immuno-positivity was scored by the percentage of positive staining cells in randomly selected fields (Labelling index). The correlation of FSCN1, TNFRSF12A and Ki-67 expressions and clinicopathological parameters with OSCC relapse were analysed by Chi-square test. Binary logistic regression was performed to predict the relationship of OSCC relapse and the significantly associated parameters. Results: Our results showed that expression of FSCN1, TNFRSF12A and Ki-67 in histologically non-involved mucosal surgical margins was weak to moderate in both study and control groups. OSCC relapse in this study was significantly associated with patients’ age (p < 0.001), pattern of invasion (p = 0.007), Chinese ethnicity (p =0.013), presence of epithelial dysplasia (p < 0.001), and alcohol consumption habits (p = 0.025). Age was the only predictor of relapse from the binary logistic regression analysis with an 11-fold risk of OSCC relapse noted in relation to patients who were aged above 57.5 years. Conclusion: The expression of FSCN1, TNFRSF12A and Ki-67 in histologically non-involved mucosal surgical margins in the iv present study was not associated with relapse in OSCC. However, patients’ age may be a reliable predictor for OSCC relapse.